United Arab Emirates : Dubai International Financial Centre; Financial Sector Assessment Program; Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report, 2007)
This Detailed Assessment of the Observance of International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation for the Dubai International Financial Centre (DIFC) discusses the preconditions for effective securities regulations and principle-by-principle assessment. The Dubai Financial Services Authority (DFSA) has established a very impressive set of laws, regulations, and rules and policies and procedures for regulation. The DFSA has shown a commitment to bring action against those in violation of the law and its rules, and has established robust licensing processes.